Um cérebro, bilhões de neurônios, milhões de funções, cinco mentes aprendentes e um futuro que já é presente - Silva, Walberto Barbosa da (2019)
The aim of this thesis is to map structures of human cognition, built on the theoretical relations between Cognitive Sciences and Education. The guiding thread of the research was the exploration of the biological architecture involved in human learning to understand brain functioning in the teaching-learning process. The categories were initially organized in the form of mind/concept maps, built on CMAPTOOLS software developed at the IHMC - Florida Institute for Human & Machine Cognition, which belongs to the University of West Florida. The use of the tool made it possible to graphically express the conceptual and categorical structures understood as important to the study, regarding cognition and its superior and simple functions, revealing scientific plausibilities in educational research. The methodology employed - which involves mapping categories, studying and interacting them - provided us with an understanding of cognitive processes involved in formal learning. The results obtained through the interaction of the categories constitute the basis of a useful information platform for teachers to view and reflect on how to select and structure content, expanding the learning process of themselves and their students, from the perspective of cultivating the five minds to the future proposed by Gardner (the disciplined mind, the synthesizing mind, the creative mind, the respectful mind, and the ethical mind). By organizing the categories related to brain morphology, to cognitive functions and to the minds necessary for future education, the study provides teachers with elements of reflection on the need to advance towards understanding the importance of cognitive neuroscience for education and the indispensabilty to innovate in their practices. The results achieved open new scientific horizons for educational research.